Sociocultural and environmental aspects of the community Souza Lima, in Várzea Grande -MT - Pinheiro, Marionil Fátima Simão; Valentini, Carla Maria Abido; Faria, Rozilaine Aparecida Pelegrine Gomes de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
he aim of this study was recording the lifestyle and the ethnic knowledge acquired over time of the traditional community Souza Lima, in Várzea Grande -MT. The study was conducted from July to September, 2014, with twelve former residents of the community. It was used the method of semi-structured interviews with open and closed questions and guided tours to record the species used in their landscape units. Respondents revealed the importance of the location and their home for their own identity and also addressed issues related to sanitation, medical care, saints’ parties and the uses of their landscape units, especially gardens and plants grown in them. The most cited family (13.85%) was the Asteraceae and the most reported use category (76.19%) corresponds to medicinal plants. The most used way ofpreparation is tea (46.55%) and the predominant use of medicinal species is for diseases of the digestive system. It was concluded that there are still in the community relatives of the first residents who have lived in the area and that there are few who manage to keep their landscape units due to old age and to survive of its most striking cultural activities: candy and hammock manufacture.